2022
DOI: 10.3389/fimmu.2022.928501
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of two COVID-19 vaccines used in India: An observational cohort study in health care workers from a tertiary care hospital

Abstract: COVID-19 pandemic witnessed rapid development and use of several vaccines. In India, a country-wide immunization was initiated in January 2021. COVISHIELD, the chimpanzee adenoviral-vectored vaccine with full-length SARS-COV-2 spike insert and COVAXIN, the whole virus-inactivated vaccines were used. To assess and compare immune response of health-care-workers to COVISHIELD (n=187) and COVAXIN (n=21), blood samples were collected pre-vaccination, 1month post-1/post-2 doses and 6months post-dose-2 and tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…In every virus variant tested, Covishield TM elicited higher responses than Covaxin â . The superiority of vectored vaccines over inactivated vaccines for antibody responses against SARS-CoV-2 has been demonstrated by other studies [7][8][9][10][11] . Further, inactivated viral vaccines have historically been of lower immunogenicity, requiring 4 doses in the primary series for the inactivated polio vaccine and the rabies vaccine.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In every virus variant tested, Covishield TM elicited higher responses than Covaxin â . The superiority of vectored vaccines over inactivated vaccines for antibody responses against SARS-CoV-2 has been demonstrated by other studies [7][8][9][10][11] . Further, inactivated viral vaccines have historically been of lower immunogenicity, requiring 4 doses in the primary series for the inactivated polio vaccine and the rabies vaccine.…”
Section: Discussionmentioning
confidence: 78%
“…Prior studies comparing Covishield TM and Covaxin â were limited to addressing only antibody responses and in particular in the health care worker population who were immunized prior to the delta wave [7][8][9][10][11] (See Supplementary Table 1). There is however, limited data on cellular immune responses elicited by these vaccines and no direct headto-head comparisons or stratification by pre-vaccination serostatus 11 . Vaccination following exposure to the Delta or Omicron variants of SARS-CoV-2 is likely to affect the quality, quantity and duration of immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Vidya Arankalle et al found that at 6 months of post vaccination, 71.7% COVISHIELD and 0% COVAXIN recipients were Nab-positive. 11 The variation of persistence of Nab could probably because of the efficacy variation of the subjected vaccine candidates & demographic dynamics of the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively low percentage of Nab in our study probably because of lower number of study subjects.In this context study by Vidya Arankalle et al reported lower titre of Nab in both the pre & post vaccination infective individual in comparison to Covishield Vs Covaxin vaccinees, the study group found significant(p<0.001) in this. Though it was mentioned that the study group among Covaxin vaccinees was comparatively lower 11.…”
mentioning
confidence: 97%
“…The samples used for this study represent a subset of samples collected earlier for the evaluation of the immune response of healthcare personnel to COVID-19 vaccinees ( 21 ). Of these, samples with sufficient volumes (n=135) were selected for the study.…”
Section: Methodsmentioning
confidence: 99%